Sexual exposure to hiv infection during the covid-19 pandemic in men who have sex with men (Msm) - de Sousa, Alvaro Francisco Lopes (2021)
Funding Information: Conselho Nacional de Pesquisa?CNPq. Process: 159908/2019-1. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.